TERMINAL ZAGREB ECCENTRICITY INDICES OF LINE GRAPHS - Revankar, Deepak S (Journal of Global Research in Mathematical Archives(JGRMA), 2016)
Terminal Zagreb eccentricity indices were proposed analogously to Zagreb eccentricity indices. For a connected graph, the first Terminal Zagreb eccentricity index is defined as the sum of the squares of the eccentricities of the terminal vertices, and the second Zagreb eccentricity index is defined as the sum of the products of the eccentricities of all pairs of terminal vertices. In this paper we obtain results for the terminal Zagreb eccentricity indices of line graphs